MODEL LAYANAN BIMBINGAN DAN KONSELING UNTUK MENANGANI DAMPAK TRAUMA - Dewi Justitia (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
The purpose of this study was to develop guidance and counceling model for the children suffering from traumatic effect resulted from domestic violance. Using Art and Play Therapy, this study was conducted in March through May 2012 at Junior Secondary School, No. 92, Jakarta. The research method employed was single subject and it was found out the decrease of traumatic anxiety which was measured with anxiety thermometer. At the end of the intervention, the data showed that the subject got deeper insight of the domestic violance causes and had ability to avoid the violance done by his/her father.